2021
DOI: 10.1027/0227-5910/a000720
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation Among Medical Students in Dammam, Saudi Arabia

Abstract: Abstract. Background: Medical students are at high risk of suicidal ideation. Aim: We aimed to obtain information on suicidal ideation among medical students in Dammam located in the Eastern Province of Saudi Arabia. Method: This cross-sectional study was conducted at the College of Medicine affiliated with Imam Abdulrahman Bin Faisal University in the Eastern Province of Saudi Arabia. Suicidal ideation in the past 12 months was assessed based on responses to four questions in the depression subscale of the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Only 4 studies found higher rates of suicidality in females than males [26,56,63]; the remainder showed no significant differences [24,29,48,49,55,60,61,64,65,93]. Two studies found males to be associated with greater suicidal behaviour [28,31].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 studies found higher rates of suicidality in females than males [26,56,63]; the remainder showed no significant differences [24,29,48,49,55,60,61,64,65,93]. Two studies found males to be associated with greater suicidal behaviour [28,31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Some papers posited that program choice may affect risk of suicidal ideation [70,76], whereas others argue that there is no significant relationship [63,71]. Most studies agree that studying medical sciences are a particularly high-risk group [26,28,31,60,70]. Level of education, specifically earlyyear and bachelor level, was also significantly correlated to suicidal ideation [26,63,70].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…There is evidence that psychological distress and loneliness increase the chances of contemplating or attempting suicide. Madadin et al conducted a 2021 study in the Eastern Province of Saudi Arabia and found that approximately one in three medical students in the study had suicidal ideations in the past 12 months, while around 40% had suicidal thoughts throughout their lives [ 12 ]. This issue can be accentuated by its association with confidentiality, time constraints, and the potential negative impact on healthcare worker careers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been some reports about suicide ideation in Saudi Arabia, the precise prevalence is yet unknown. A small descriptive study aimed at assessing the prevalence of suicidal thoughts among medical students in the Eastern Province of Saudi Arabia reported that 42.2% had suicidal ideation in their lifetime, and 35.4% reported thoughts of suicide within the last 12 months [ 12 ]. Another study conducted in Abha found that among dental students, 43.5% had suicidal ideation in their lifetime, 30.7% reported it in the last 12 months, and 15.1% reported attempting suicide [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students have a prevalence of SI from 13.7 to 33.3% (4)(5)(6). Due to the COVID-19 pandemic, not only was physical health affected (7)(8)(9), but mental health has also deteriorated significantly in various populations (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%